2019
DOI: 10.1042/bst20190316
|View full text |Cite|
|
Sign up to set email alerts
|

Glutamate transporters: a broad review of the most recent archaeal and human structures

Abstract: Glutamate transporters play important roles in bacteria, archaea and eukaryotes. Their function in the mammalian central nervous system is essential for preventing excitotoxicity, and their dysregulation is implicated in many diseases, such as epilepsy and Alzheimer's. Elucidating their transport mechanism would further the understanding of these transporters and promote drug design as they provide compelling targets for understanding the pathophysiology of diseases and may have a direct role in the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Then, over almost two decades, other 3D structures of GLT Ph in different conformations have been solved, together with those of other bacterial transporters for glutamate/aspartate, such as GLT tk . 2,7,30 These studies confirmed the homotrimeric architecture and gave further insights into the molecular determinants of the transport mechanism and allowed studying the human members of the SLC1 family by homology modeling coupled to biochemical approaches. 3133 Later, in 2017, the 3D structure of the human isoform of EAAT1 was solved, demonstrating that the eukaryotic proteins show the same homotrimer organization as the bacterial counterparts; since then, more refined homology models have been built for the other members of the SLC1 family, including ASCT2.…”
Section: Structural and Functional Featuresmentioning
confidence: 61%
See 3 more Smart Citations
“…Then, over almost two decades, other 3D structures of GLT Ph in different conformations have been solved, together with those of other bacterial transporters for glutamate/aspartate, such as GLT tk . 2,7,30 These studies confirmed the homotrimeric architecture and gave further insights into the molecular determinants of the transport mechanism and allowed studying the human members of the SLC1 family by homology modeling coupled to biochemical approaches. 3133 Later, in 2017, the 3D structure of the human isoform of EAAT1 was solved, demonstrating that the eukaryotic proteins show the same homotrimer organization as the bacterial counterparts; since then, more refined homology models have been built for the other members of the SLC1 family, including ASCT2.…”
Section: Structural and Functional Featuresmentioning
confidence: 61%
“…36 This observation, supported by structural analyses, still requires experimental pieces of evidence to be definitively confirmed. 6,39 The one-gate elevator mechanism is shared by all the SLC1 family members; 2,7 during the cycle, the substrate is occluded in the transport domain that performs a large movement from the extracellular to the intracellular milieu and vice versa ( Fig. 3 ).…”
Section: Structural and Functional Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to prevent excessive glutamate levels outside of nerve cells, the body maintains normal glutamate levels through the glutamate receptor. Glutamate transporters may be divided into a variety of types, such as excitatory amino acid transporters (EAAT) and vesicle glutamate transporters, according to their structural and functional characteristics ( 27 , 28 ). Glutamate/L-aspartate transporter (GLAST) is a subtype of EAAT, also known as EAAT1, mainly distributed on Müller cells in the retina ( 29 ).…”
Section: Kir41 and The Retinal Microenvironmentmentioning
confidence: 99%